Serotype distribution and antimicrobial Susceptibility of Streptococcus pneumoniae isolated from patients with pneumococcal pneumonia - Hamzagić Farah; Ranin Jovana; Gajić Ina; Opavski Nataša; Ranin Lazar (Medicinski Podmladak, 2021)
Introduction: Streptococcus pneumoniae is a major cause of community-acquired pneumonia (CAP). In Serbia, pneumococcal conjugate vaccines PCV-10 and PCV-13 were licensed for immunization in 2018. Aim: The aim of this study was to evaluate serotype distribution and antimicrobial susceptibility of S. pneumoniae isolated from patients with pneumococcal pneumonia. Material and methods: Isolates of S. pneumoniae were recovered from patients with CAP addmitted to 18 hospitals throughout Serbia from 2012-2020. Confirmation of the identification was performed using lytA gene detection by PCR. Serotyping and antimicrobial susceptibility testing was performed by Quellung reaction and disk diffusion/gradient test, respectively. Interpretation of the susceptibility testing was done according to the current European Committee on Antimicrobial Susceptibility Testing recommendations. Results: During the study period, a total of 100 isolates of S. pneumoniae were collected. Overall, 19 pneumococcal serotypes were identified. The predominant types observed, in order of decreasing frequency, were 3 (37%), 14 (16%), 6B (6%), 7F (5%), 9V (4%), and 4 (4%); further, 2% of the isolates were non-typeable. However, the most common serotype among children < 2 years old was 14 (27.3%). The vaccine coverage of strains isolated from children < 5 years was higher with PCV-13 compared to PCV-10 (86,7% vs. 46,7%, p = 0.008). Additionally, the vaccine coverage of pneumococci isolated from patients >2 years was higher with the PPV-23 than with PCV-13 (96.6% vs. 84.3%, p = 0.0230). Ten isolates (10%) were PPV-23/nonPCV-13, whereas four isolates (4%) were non-typable (17A, 23A, and 9A). Serotype 3 significantly increased from pre-vaccine to post-vaccine period (30.8% vs. 60.8%, p = 0.0108). The overall antimicrobial resistance rates were as follows: penicillin - 9%, ceftriaxone - 2%, erythromycin - 24%, clindamycin - 16%, tetracycline - 11%, and trimethoprim-sulfamethoxazole - 21%. Conclusion: More than 70% of the isolated strains belonged to the serotypes 3, 14, 6B, 9B, and 4. The highest resistance rates of the tested pneumococci were found for macrolides and trimethoprim-sulfamethoxazole.